DIFFERENTIAL INVOLVEMENT OF AMYGDALAR NMDA RECEPTORS ACROSS VARIANTS OF CONTEXTUAL FEAR CONDITIONING IN ADOLESCENT RATS - Miller, Lauren A. (Behav Brain Res, 2018)
In standard contextual fear conditioning (sCFC), learning of the context and formation of the context-shock association occur in the same training session whereas in the context preexposure facilitation effect (CPFE) learning the context (preexposure) and the context-shock association (training) are separated by 24 hours. In both procedures conditioned freezing can be measured immediately (post-shock test) or during a 24-hour retention test. In adult rats, disrupting basolateral amygdala (BLA) activity or plasticity during training on sCFC impairs both post-shock and retention freezing [Maren et al, 1996; 1]. This manipulation on the training day of the CPFE disrupts retention freezing but effects on post-shock freezing are unknown [Matus-Amat et al, 2007; 2]. Experiment 1 extended this literature from adult to adolescent rats and to the role of BLA activity and plasticity in post-shock freezing during the CPFE. Intra-BLA infusions of muscimol prior to the training day of the CPFE disrupted both post-shock and retention freezing in Postnatal Day (PD) 31-33 rats. In the second two experiments, intra-BLA infusions of APV prior to training day of sCFC disrupted retention but not post-shock freezing, while infusions of APV prior to training of the CPFE disrupt both post-shock and retention freezing. Our findings suggest that the BLA plasticity plays a different role in the CPFE vs. sCFC. Its role in the CPFE is similar in both adolescent and adult rats, while the role of the BLA in post-shock freezing during sCFC may differ across age or across studies that employ different procedures or parameters.